380 Preliminary results of an ongoing phase I trial of FT500, a first-in-class, off-the-shelf, induced pluripotent stem cell (iPSC) derived natural killer (NK) cell therapy in advanced solid tumors. (10th December 2020) - Hong, David; Patel, Sandip; Patel, Manish; Musni, Kimberly; Anderson, Marlisa; Cooley, Sarah; Valamehr, Bahram; Chu, Wayne
Abstract : Background: FT500 is an investigational, off-the-shelf NK cell cancer immunotherapy derived from a human clonal master iPSC line, a renewable cell source from which innate effector cells can be mass produced and made available off-the-shelf for broad patient access and multiple dose administration. FT500 has potent innate cellular cytotoxicity as compared to NK cells sourced from healthy donors and has been shown to synergize with T cells and anti-PD-1 blockade in preclinical studies. 1 Methods: FT500 is being investigated in a Phase I clinical trial as monotherapy and in combination with immune checkpoint inhibitors (ICIs) in patients with advanced solid tumors and lymphomas (ClinicalTrials.gov: NCT03841110 ). Treatment consists of 2 days lympho conditioning (fludarabine 25 mg/m 2 and cyclophosphamide 300 mg/m 2 ) followed by 2 cycles of 3 once weekly doses of FT500 as monotherapy or combined with 1 of 3 approved ICIs (nivolumab, pembrolizumab, or atezolizumab) in patients who have failed prior ICI therapy. Key clinical and translational readouts include FT500 safety and tolerability, including immune mediated toxicities and anti-product immunogenicity. Results: 15 patients with relapsed/refractory disease following a median of 4 prior therapies were treated in dose escalation, including 9 with FT500 monotherapy (3 with 1×108 cells, 6 with 3×108 cells) and 6 with FT500 (3 each with 1×108 and 3×108 cells) combined with ICI. No dose limiting toxicities, Grade ³3 related adverse events (AEs), Grade ³3 related serious AEs, or related AEs leading to treatment discontinuation were reported. No graft-versus-host disease (GvHD), cytokine release syndrome (CRS), or neurotoxicity (NT) was observed. The most common treatment-emergent AEs in >3 patients were nausea (9), fatigue (7), constipation, decreased appetite, decreased lymphocyte count, decreased white blood cell count (5 each), anemia, and decreased neutrophil count (4 each). Nine of 13 efficacy-evaluable solid tumor patients had best response of stable disease by iRECIST. One patient with classical Hodgkin lymphoma (cHL) refractory to prior experimental anti-PD-1 therapy had a 58% reduction in target lesions size following FT500 plus ICI. No evidence of robust B- or T-cell mediated anti product responses was observed despite endogenous immune cell recovery following lympho-conditioning. Conclusions: Administration of 6 doses of up to 3×108 FT500 cells is safe and tolerable without evidence of GvHD, CRS, NT, or host immune rejection. Enrollment of advanced non-small cell lung cancer and cHL patients at 3×108 FT500 cells per dose combined with ICI is ongoing. Ethics Approval: This study is being conducted in accordance with the Declaration of Helsinki and was approved by all Institutional Review Boards from each clinical site participating in the study. Specific approval numbers can be provided upon request. Reference: Cichocki F, Bjordahl R, Gaidarova S, Mahmood S, Rogers P, Ge MQ, Kaufman DS, Cooley S, Valamehr B, Miller JS. iPSC-derived NK cells and anti-PD-1 antibody synergize to enhance T cell cytokine and cytolytic responses against multiple tumors. Blood 2018;132(Supplement 1):730.